SOSIALISASI SEMBOYAN DAN RAMBU LALU LINTAS BAGI PENJAGA PINTU PERLINTASAN SEBIDANG KERETA API (Politeknik Perkeretaapian Indonesia Madiun, 2022)
The implementation of this community service aims to increase theunderstanding of railroad crossing gate guards so that they can understandthe importance of slogans and traffic signs. This activity was attended byseveral 24 participants who took part in PJL training in the East Java region. Theactivity was carried out by providing material in the form of learning modulesand direct practice at the Indonesian Railways Polytechnic. To find out theresults of participants' understanding of the material that has been taught, pretest and post-test were given. The results of this activity can improveperformance in the form of understanding the importance of slogans andtraffic signs at railroad crossings to officers who take part in guarding crossinggates.